2014
DOI: 10.1016/j.microc.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of HS-SPME analytical conditions using factorial design for trihalomethanes determination in swimming pool water samples

Abstract: a b s t r a c t Trihalomethanes (THMs) are widely referred and studied as disinfection by-products (DBPs). The THMs that are most commonly detected are chloroform (TCM), bromodichloromethane (BDCM), chlorodibromomethane (CDBM), and bromoform (TBM). Several studies regarding the determination of THMs in swimming pool water and air samples have been published. This paper reviews the most recent work in this field, with a special focus on water and air sampling, sample preparation and analytical determination me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, the fibre coating might begin to lose its ability to adsorb analytes at higher temperatures. This effect can result in a decrease in the extraction of volatile compounds, as seen at temperatures >45°C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fibre coating might begin to lose its ability to adsorb analytes at higher temperatures. This effect can result in a decrease in the extraction of volatile compounds, as seen at temperatures >45°C .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to reducing the time spent on the experiments, response surface optimization has a number of tests to determine the optimum level that are often consistent with the actual conditions of the analyses . Because the analysis by SPME involves a number of factors, the use of factorial design associated with the response surface analysis has been applied in different optimizations that include the pesticide residue analysis in fruits and vegetables , trihalomethanes in swimming pools , heterocyclic compounds in wines , aromatic compounds in cooked meat and carbonyl compounds in beer , among others. The present study sought to evaluate the influence of the extraction temperature, extraction time and desorption time on the analysis of volatile compounds in cachaça samples and optimize the extraction conditions by the use of response surface methods.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on mVOCs highlight the use of headspace-solid phase micro-extraction (HS-SPME) as appropriate tool to obtain the compounds under relatively mild conditions. The extraction occurs in the absence of solvents and it is based on the partition equilibrium of analytes between the sample matrix and the extraction phase [18,19]. Different types of mixed fibers can be used as matrix, including polydimethylsiloxane-divinylbenzene-carboxene (PDMS/DVB/CAR), polydimethylsiloxanedivinylbenzene (PDMS/DVB) and polydimethylsiloxane-carboxene (PDMS/CAR).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that use of solid phase microextraction (SPME) technique affords the possibility of sampling THM analytes by either method (spot [16][17][18] and TWA [19][20][21]) with easy incorporation to subsequent GC/MS analysis. Work by Stack [22] and Valencia [23] have shown the utility of headspace-(HS-) SPME with GC/MS for measurement of THMs from swimming pools and chlorinated drinking waters.…”
Section: Introductionmentioning
confidence: 99%